Colin McCahon : a question of faith - Bloem, Marja; Bail, Murray; Browne, Martin; Fuchs, Rudi H.; McCahon, William; Miller, Steven; Pound, Francis; Stedelijk Museum Amsterdam; City Gallery, Wellington; Auckland Art Gallery Toi o Tamaki, Auckland; National Gallery of Victoria, Melbourne; Art Gallery of New South Wales, Sydney (St. Nelson (New Zealand) : Craig Potton Publishing, 2002)
Colin McCahon is the first modern New Zealand painter of major international importance. Particularly since his death in 1987, he has become a legendary figure, with his work and life the subject of much discussion and research. Outside of Australasia however, McCahon has remained almost unknown and his achievement largely unrecognised. Inspired by the conviction that McCahon deserves to be acknowledged as a major 20th Century artist. In August 2002 the Stedelijk Museum Amsterdam opened the exhibition Colin McCahon : A Question of Faith. The largest and most significant retrospective yet devoted to McCahon. A Question of Faith focuses on two issues central in the artist's oeuvre - his personal exploration of spirituality and religious faith, and his depiction of the New Zealand landscape. Published to coincide with Colin McCahon : A Question of Faith, this book is both the catalogue for the exhibition and more besides. The most significant publication on McCahon for many years, it has at its heart reproductions of the 78 paintings in the exhibition, augmented by a further 112 illustrations of artworks and historical photographs. Essays by the exhibition's curator Marja Bloem, the artist's son William McCahon, the Australian writer Murray Bail and the New Zealand art historian Francis Pound, address the themes of the exhibition. These texts are supported by an extensive chronology of McCahon's life (including excerpts from many key writings both by and about the artist), an up-to-date bibliography, and the first comprehensive listing of McCahon's solo and selected group exhibitions. This landmark publication is and will remain essential reading for anyone interested in the life and works of this visionary artist.
Colin McCahon : a question of faith, Stedelijk Museum, Amsterdam, 30 August - 10 November 2002 / traveling to City Gallery, Wellington (New Zealand), Auckland Art Gallery Toi o Tamaki, Auckland (New Zealand), National Gallery of Victoria, Melbourne (Australia) and Art Gallery of New South Wales, Sydney (Australia) during 2002-2004
Chronology p. 159-239
bibliog., filmog. p. 240-251
ind. tent., gr. tent. p. 252-264
Engels
boek
Keywords: McCahon, Colin; Nieuw-Zeeland